Analisis Tingkat Kerentanan Longsor Daerah Muara Sungai Bone Kota Gorontalo - Muhammad Iqbal Asiki; Sri Maryati; Noviar Akase (Jambura Geoscience Review, 2019)
In Gorontalo City there have been 11 landslides in 2017 which are spread in 3 sub-districts namely Hulonthalangi, Kota Barat, and Dumbo Raya. While in 2018 there was a landslide in Tenda village which claimed two lives. The research site is located in coordinate 00°29'00" - 00°31’51" N and 123°3'00" - 123°5'27"  E with the wide of area 2,531 Ha consisting of 1,745 Ha of the mainland and 786 Ha of the sea. The research area administratively is located in Dumbo Raya Sub-district, Gorontalo city, Gorontalo Province. The purpose of this study was to determine the level of landslide susceptibility in the study area and make zonation maps of landslide prone area.  This research method applied in this study was integration of field survey and GIS analysis. The parameters which influence the landslide are lithology, precipitation, slope, lineament density, type of soil, and the land use. Based on the analysis of landslide susceptibility, the level of susceptibility in the research site consists of 3 classes; low, moderate, and high. The low class of landslide susceptibility has the area of 217.46 Ha, the moderate class of landslide susceptibility has the area of 338.93 Ha with the biggest spread is in Leato Selatan village; 102.68 Ha. The high class of landslide susceptibility has the area of 1,188.70 Ha with the biggest spread in Leato Selatan Village; 288.66 Ha.